Presynchronizing injections of prostaglandin F[subscript]2alpha[subscript] or prostaglandin F[subscript]2alpha[ subscript + Gonadotropin-releasing hormone before a fixed time artificial insemination CO-Synch + CIDR program in suckled beef cows - Hill, Scott L. (Kansas State University, 2013)
We hypothesized that pregnancy outcomes may be improved by inducing luteal regression, ovulation, or both before a control CO-Synch + CIDR program (100 mcg GnRH i.m. [GnRH-1] and insertion of a progesterone-impregnated intravaginal controlled internal drug release [CIDR] insert on d -10, 25 mg PGF2alpha (PG) i.m. and CIDR insert removal on d -3, and 100 mcg GnRH i.m. [GnRH-2] and timed AI [TAI] on d 0) in suckled beef cows. This hypothesis was tested in 2 experiments, in which cows were treated with either PG or PG + GnRH before initiating a control CO-Synch + CIDR program to increase the proportion of cows starting the program in a low (< 1 ng/mL; Exp. 1) or high (≥ 1 ng/mL; Exp. 2) progesterone status, respectively. Blood was collected before each injection for later progesterone analyses. In Exp. 1, cows at 9 locations (n = 1,537) were assigned to either: (1) control or (2) PrePG (same as control with a PG injection on d -13). The PrePG cows had larger (P < 0.05) follicles on d -10 and more (P < 0.05) ovulated after GnRH-1 than controls (60.6 vs. 36.5%). Incidence of estrus between d -3 and 0 was greater (P < 0.05) for treated multiparous cows than multiparous controls and treated and control primiparous cows (74.1 vs. 64.3, 58.6, and 59.1%, respectively). In Exp. 2, cows at 4 locations (n = 803) were assigned to: (1) control (same as Exp. 1) or (2) PrePGG (same as control with PG injection on d -20 and GnRH injection on d -17. Cows with BCS > 5.0 or ≥ 70 d postpartum at TAI were more (P < 0.05) likely to become pregnant than thinner cows or those with fewer days postpartum. Treated cows in both experiments were more (P < 0.05) likely than controls to have luteolysis after initial PG injections and reduced (P < 0.05) serum progesterone. In both experiments, pregnancy rates at d 35 did not differ between treatment and control; however, cows classified as anestrous before d -10, but with elevated progesterone on d -10, had increased (P < 0.05) pregnancy outcomes than remaining anestrous cows with low progesterone concentrations. In summary, luteal regression and ovulation were enhanced by treatments before the 7 d CO-Synch + CIDR program; however, pregnancy per TAI was not improved.
Keywords: Timed aritificial insemination; Presynchronization; Luteolysis; Ovulation; Follicular wave; Artificial insemination; Animal Sciences (0475)